Playing on life’s terms: Behavioral strategies for changing situations - Wiik, Elisa; Alha, Kati (Eludamos: Journal for Computer Game Culture, 2023)
This article sheds light on the changes to play habits when there is not as much time or possibilities to play as before. The research is based on a survey and interviews of Finnish former active players, who now played less or had quit some game types they used to enjoy. Most of the respondents still played something, but the playing had changed on the level of games, playstyles, time management, and content. These changes were then used as behavioral strategies to keep gaming as a part of the changing lives: shifting to lighter options, integrating playing into everyday life, redefining co-play, and focusing on opportunities. The results highlight the complexity and continuity of the changes and negotiations, and further hint at how the borders of casual and hardcore playing are fluid and mixed. This complexity and fluidity of play should be the starting point of a game design that must be heard in the public and academic discourses around gaming.